The role of patient-provider interactions: Using an accounts framework to explain hospital discharges against medical advice. (May 2016) - Lekas, Helen-Maria; Alfandre, David; Gordon, Peter; Harwood, Katherine; Yin, Michael T.
Abstract: The phenomenon of leaving the hospital against medical advice (AMA) despite being quite common and associated with significant deleterious health outcomes remains inadequately understood and addressed. Researchers have identified certain patient characteristics as predictors of AMA discharges, but the patients' reasons for these events have not been comprehensively explored. Moreover, because the medical authority model dominates this research area, providers' experiences of AMA discharges remain unstudied. We examined the AMA discharge from a patient-centered perspective by analyzing the content of notes providers generate to record such events. We analyzed providers' notes for all inpatients with a primary HIV diagnosis (N = 33) that, in 2012, left an urban hospital AMA. Applying the Scott and Lyman accounts framework, we identified that the notes constituted records of providers' and patients' excuses and justifications for failing to meet the expectations of a provider offering patient-centered care and a compliant patient receiving care. Alongside the patients' reasons for leaving AMA, the notes also revealed the providers' reasons for honoring or discrediting the patients' accounts. The style of the accounts and the professional status of the notes' authors enabled us to contextualize the production and sharing of AMA notes in the hospital hierarchy. Conceptualizing AMA notes as dyadic accounts elicited specific factors that challenge the patient-provider relationship, and generated insights on how to strengthen it, and thus decrease the rates of AMA discharges and their associated health effects. Highlights: Analyzing patient discharge against medical advice through an accounts framework. Provider AMA discharge notes offer data on the provider and the patient experience. AMA discharge notes include insights on enhancing the patient-provider relationship. AMA discharge notes reveal patient excuses and justifications for wanting to leave. AMA discharge notes reveal provider excuses and justifications for the AMA event.